2020
DOI: 10.1002/chem.201905601
|View full text |Cite
|
Sign up to set email alerts
|

The Coordination Behaviour of CuI Photosensitizers Bearing Multidentate Ligands Investigated by X‐ray Absorption Spectroscopy

Abstract: A systematic series of four novel homo‐ and heteroleptic Cu I photosensitizers based on tetradentate 1,10‐phenanthroline ligands of the type X^N^N^X containing two additional donor moieties in the 2,9‐position (X=SMe or OMe) were designed. Their solid‐state structures were assessed by X‐ray diffraction. Cyclic voltammetry, UV‐vis absorption, emission and X‐ray absorption spectroscopy were then used to determine their electrochemical, photophysical and structural features in solution. Fol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
25
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 19 publications
(29 citation statements)
references
References 111 publications
4
25
0
Order By: Relevance
“…However, the Cu−N bonds of the cuprates are about 0.13 Å shorter, than in the respective [Cu(I)(xantphos)(4 H ‐imidazolato)] complexes [37] . This observation is in agreement with reports on Cu(I)‐phenanthroline complexes [19,38,39] where similar bond length differences of about 0.1 Å were observed. These differences mainly attributed to the steric bulk of the xantphos ligand.…”
Section: Resultssupporting
confidence: 91%
“…However, the Cu−N bonds of the cuprates are about 0.13 Å shorter, than in the respective [Cu(I)(xantphos)(4 H ‐imidazolato)] complexes [37] . This observation is in agreement with reports on Cu(I)‐phenanthroline complexes [19,38,39] where similar bond length differences of about 0.1 Å were observed. These differences mainly attributed to the steric bulk of the xantphos ligand.…”
Section: Resultssupporting
confidence: 91%
“…[24,90] The structure of this complex in the triplet excited state was investigated in pioneering XAS experiments, [52,91] later [Cu-(dmp) 2 ] + and its derivatives were further investigated utilizing pump-probe X-ray spectroscopy. [75,[92][93][94][95][96] A previous review [97] summarizes early progress in this field and we will focus on the findings reported in recent articles. [75,94,98,99] For homoleptic diimine Cu(I) complexes, the photoexcitation induces Jahn-Teller distortions around the metal center and the initially tetrahedral configuration flattens.…”
Section: Pump-probe Xas Study Of Mononuclear Cu Complexesmentioning
confidence: 99%
“…The copper site can be additionally coordinated in the excited state not only by the solvent molecule but also intramolecularly by suitable coordinating moieties present in the ligand scaffold. For example, for related derivatives of [Cu(dmp) 2 ] + with −CH 2 OCH 3 or −CH 2 SCH 3 in the 2 and 9 position of the phenanthroline ligand, five‐coordinated excited states were observed (Figure 6a) [94] . Naturally, a −OMe or −SMe donor, respectively, of one of the substituents is pre‐aligned closely to the Cu center already in the ground state and after photoexcitation the corresponding distances became shorter: Cu−O 2.29 Å and Cu−S 2.47 Å.…”
Section: Pump‐probe Xas Study Of Mononuclear Cu Complexesmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, Moonshiram and coworkers investigated the influence of two additional donor moieties (SMe or OMe at the 2,9‐position of the 1,10‐phenanthroline) on the excited states of the homoleptic Cu I photosensitizers by picosecond TR‐XAS. [ 52 ] By replacing one of the diimine donors with a bulky diphosphine xantphos, four novel homo‐ and heteroleptic copper photosensitizers (C1–C4) were compared to systematically elucidate the impact of steric and electronic effects on the excited states. Figure a shows the transient spectra (laser on–off) at an averaged time delay of 80 ps.…”
Section: Electronic and Structural Dynamics Of Light‐harvesting Unitmentioning
confidence: 99%